The Quest for the Good Life in Precarious Times Ethnographic Perspectives on the Domestic Moral Economy - Gregory, Chris; Altman, Jon (ANU Press, 2018)
The study of the quest for the good life and the morality and value it presupposes is not new. To the contrary, this is an ancient issue; its intellectual history can be traced back to Aristotle. In anthropology, the study of morality and value has always been a central concern, despite the claim of some scholars that the recent upsurge of interest in these issues is new. What is novel is how scholars in many disciplines are posing the value question in new ways. The global economic alignments of the present pose many political, moral and theoretical questions, but the central issue the essays in this collection address is: how do relatively poor people of the Australia-Pacific region survive in current precarious times? In looking to answer this question, contributors directly engage the values and concepts of their interlocutors. At a time when understanding local implications of global processes is taking on new urgency, these essays bring finely honed anthropological perspectives to matters of universal human concern-they offer radical empirical critique based on intensive fieldwork that will be of great interest to those seeking to comprehend the bigger picture.